The Scholar Transport Programme in the Eastern Cape : a case study of the beneficiaries at a secondary school in the Idutywa district. - Bingma, Vangile Danielle (University of Pretoria, 2018)
This study investigated the perceptions of the beneficiaries of a learner transport programme in the Idutywa District of the Eastern Cape. Learner transport in South Africa continues to be a challenge, especially for those in the rural areas. The Statistics South Africa General Household Survey (2016:14) reported that more than two thirds (69.8%) of learners walked to school and 83.6% of these learners needed 30 minutes or less to get to school. Many learners in the rural areas still walk long distances to access schools due to poor infrastructure and the limited number of easily accessible schools. To understand the beneficiaries’ perceptions, a qualitative case study of a secondary school in the rural Eastern Cape village was designed. Data was collected through 47 face-to-face interviews with learners, teachers, parents, a principal as well as through a telephone interview with a government official. Additionally, observations were undertaken to gather supplementary data focusing on the geography of the village as well as the arrival and departure times of the school transport. The study draws on a social policy framework to make sense of the study findings. Through a thematic analysis of the data, themes such as spaces of operation, learners’ travelling experiences, schooling barriers as well as unintended consequences of the learner transport programme were arrived at. Although the transport provided much needed relief, findings indicate that learners still walk to school if the transport does not pick them up as scheduled and they often do not have money for public transport. They also got to school late when they had to walk to school, there is a shortage in the number of vehicles assigned to transport them, learners also missed extra lessons due to the pick-up and departure times of the transport and there is occasional conflict amongst the learners using the learner transport. The study concludes that there needs to be an increased provision of the government learner transport, work needs to be done regarding the implementation of the Learner Transport Policy, as well as the management of the programme in rural villages such as the one that the study focused on in Eastern Cape.